(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Customer complaints will unavoidably occur, no matter how effective the business is. If there’s an overlooked or dismissed complaint, it may seem to effectively tell the client that their comments were not valued. Many business owners consider handling complaints to be a time- consuming and irritating process. However, by developing an efficient method, problems may be resolved quickly and easily. Even though we are aware that Filipinos have high expectations for services, it is vital to handle complaints that travelers lodge with hotels all over the Philippines. Particularly when their complaint was not promptly resolved. Typically, some visitors may complain about your hotel on social media. It is not desired. The hotel’s staff, as well as guests, will be affected. This study reveals that amenities can also cause vexation of the guests while on their premises, and the absence of personalized services in the room services may cause irritation to the guests. The overall hotel management might have a lack of knowledge in terms of operation during the guests’ stays. It can be the reason for the dissatisfaction of their guests. It is advised that the staff listen patiently, which is essential for effectively handling client issues. The staff members should be respectful and truly respond by acknowledging the difficulties raised by the guests, taking ownership of the situation, offering a solution, expressing their commitment to improving, requesting a second chance to do so, and acting in a professional manner on all platforms. In order to prevent mistakes when joining the hospitality sector, and especially the hotel industry, it is advised that the students be more educated about hotel services.